Civic Intervention Documentary: a Socio-culturally Attuned Rhetorical Address to the Neglect of South African Adolescent Orphans - Semege, Mahoro A. (My University, 2019)
In previous studies of the documentary film, a common approach speaks to the documentary’s ability to arrest social issues. This is often attributed to the documentary’s rhetorical address. But in most instances, there is a glaring oversight of the inter-affectivity between socio-cultural processes that frame social issues and the rhetorical principles of the documentary. My research sought to address that oversight. Its aim was to establish how a knowledge of socio-cultural processes that underpin a social issue could enhance the rhetorical effectiveness of a civic intervention documentary. Using the neglect of adolescent orphans as a case study, the research revealed that the neglect of these orphans is framed by public narratives deeply entrenched in socio-cultural processes. These narratives showed potential to generate cognitive biases that, if ignored, can create subliminal counter-narratives that the documentary must subvert if it is to contribute to addressing this social issue. This prompted a culturally attuned conceptualization and produc tion of a documentary film that was used to test the effectiveness of the docume ntary’s rhe torical ability to generate pledges of action against the neglect of adolescent orphans in South African communities . The results of the film’s test screenings were largely positive: the film triggered the majority of its viewers to make pledges to take part in programmes to help neglected adolescent orphans . However, for these results to be conclusive, further research on a wider scale need to be done. Such research can validate the roles of many NGOs dealing with this issue; it can be useful to governmental departments whose tasks are to find care programmes for different categories of orphans ; it would be of even greater import ance to Afrocentric film scholarship in particular and documentary film studies in general.
A thesis submitted to the Wits School of Arts, Faculty of Humanities, University of the Witwatersrand in partial fulfilment of the requirements for the degree of Doctor of Philosophy